The Framework of Urban Planning in China in the 21st Century: A Discipline at the service of Building a Nation - Masnou Morera, María José (Sinología hispánica. China Studies Review, 2021)
The character of urban planning in China must be understood within the framework of the policies of the country’s planning. In this context, urban planning is subordinate to the economic construction of the nation.The most eloquent image of this Post-Socialism scenario is the intense urbanization processes of cities. New residential areas, downtown and affluent business districts, industrial and technology parks, are its image. However, what is the planning framework, procedures and urban instruments that allow these processes? The political structure of the Chinese state centrally and hierarchically directs this planning through its state policies and guidelines of the Five-Year Plans, and its sectorial implementation through the different ministries. However, a lack of integrated planning leads to the duplicity of competencies, lack of coordination and divergence of objectives. A new framework, the ‘duoguiheyi’, tries to alleviate this situation. The land regime and its development is an essential factor to understand the transformation and growth processes of cities, as well as the entrepreneurial character of the local state. At the same time, contemporary urban planning as a discipline has a short history and a very recent legal framework that generates a lack of cases of reference and adaptation to rapid urban dynamics. In some chapters, the city of Hangzhou will serve as an explanatory reference.